The Importance of Laboratory Experience in the Engineering Curricula - Kuppuswamy, G.; Natrajan, R. (Journal of Engineering Education Transformations, 1990)
It is generally accepted that the quality of laboratory instruction is of considerable significance in engineering education . Laboratory-oriented studies include the research required to improve this process,. the use of laboratory instruction as a teaching method, characterization of the equipment and facilities, and other aids to this educational process.